2013
DOI: 10.4103/0973-6247.115566
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion transmittable infections - Seroprevalence among blood donors in a tertiary care hospital of Delhi

Abstract: Context:Transfusion transmittable infections (TTI) continue to be a major threat to safe transfusion practices. Blood is one of the major sources of transmission of infectious diseases viz. human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis, malaria, and many other infections in India. Screening assays for the infectious diseases with excellent sensitivity and specificity helps to enhance the safety of the blood transfusions reducing the diagnostic window period as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
5
12
1
Order By: Relevance
“…Pallavi et al reported HCV and HIV prevalence of 0.23% and 0.44% among blood donors from Mysore, India, 25 and Pathak et al reported 0.7% and 0.25% of HCV and HIV seroprevalence among blood donors in a tertiary care hospital in Delhi. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Pallavi et al reported HCV and HIV prevalence of 0.23% and 0.44% among blood donors from Mysore, India, 25 and Pathak et al reported 0.7% and 0.25% of HCV and HIV seroprevalence among blood donors in a tertiary care hospital in Delhi. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to vector transmission, malaria can also be transmitted by blood components, and transfusion-transmitted malaria (TTM) cases, although rare, continue to pose a risk to blood services worldwide [ 6 , 7 ]. TTM is an important public health problem, especially in populations with no immunity to malaria where it can be fatal if not recognized and treated quickly [ 8 ]. Infected blood transfusions directly release malaria parasites into a recipient’s bloodstream triggering the development of high-risk complications and potentially leading to a fatal outcome [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… with WHO standard 98–750 with similar 95% LOD to standard 97–656 were used. The risk days have been calculated for pool sizes relevant to the blood screening tests practiced in a few representative countries .…”
Section: Screening Sensitivitymentioning
confidence: 99%